The treatment of medial tibial stress syndrome in athletes; a randomized clinical trial - Moen, M. H.; Holtslag, L.; Bakker, E.; Barten, C.; Weir, A.; Tol, J. L.; Backx, F. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2012)
The only three randomized trials on the treatment of MTSS were all performed in military populations. The treatment options investigated in this study were not previously examined in athletes. This study investigated if functional outcome of three common treatment options for medial tibial stress syndrome (MTSS) in athletes in a non-military setting was the same. Methods: The study design was randomized and multi-centered. Physical therapists and sports physicians referred athletes with MTSS to the hospital for inclusion. 81 athletes were assessed for eligibility of which 74 athletes were included and randomized to three treatment groups. Group one performed a graded running program, group two performed a graded running program with additional stretching and strengthening exercises for the calves, while group three performed a graded running program with an additional sports compression stocking. The primary outcome measure was: time to complete a running program (able to run 18 minutes with high intensity) and secondary outcome was: general satisfaction with treatment. Results: 74 Athletes were randomized and included of which 14 did not complete the study due a lack of progress (18.9%). The data was analyzed on an intention-to-treat basis. Time to complete a running program and general satisfaction with the treatment were not significantly different between the three treatment groups. Conclusion: This was the first randomized trial on the treatment of MTSS in athletes in a non-military setting. No differences were found between the groups for the time to complete a running program